Leadership Practices of Elementary School Heads in Zambales: Managing Resources for Effective School Operations - Florabel A. Fababier; Marie Fe D. De Guzman; Raymond D. Espiritu (Future Science / FSH-PH Publications, 2026)
This study examines the leadership practices of elementary school heads in Zambales, focusing on how they manage financial, human, and physical resources and the impact on school operations. Using a descriptive quantitative research design, data were collected from 30 school heads and 535 teachers across various districts in Zambales. The findings reveal significant challenges, including resource misallocation, limited budgets, and complex regulatory requirements. Both school heads and teachers identified financial management as the top priority, with difficulties in budgeting, financial record-keeping, and procurement processes being the most pressing issues. In response, the study proposes an intervention program designed to improve resource management practices within schools. The program emphasizes enhancing financial transparency, setting clear performance expectations for staff, providing professional development opportunities, and fostering stronger partnerships between schools and community organizations. These strategies aim to equip school leaders with the tools to optimize resource allocation, streamline procurement processes, and improve overall operational efficiency. The study highlights the importance of effective resource management in ensuring sustainable, high-performing schools. The practical implications suggest that the Department of Education (DepEd) should prioritize district-level interventions to address the challenges identified in the study, particularly those related to financial management and leadership development. Such interventions are essential to improving resource allocation and leadership practices, ultimately enhancing school performance and student outcomes. The proposed intervention program offers a framework to overcome barriers to optimal resource management, fostering greater resource efficiency and improving school operations.